Computational linguistics and intelligent text processing : 9th international conference, CICLing 2008, Haifa, Israel, February 17-23, 2008 : proceedings - Gelbukh, Alexander (Springer, 2017)
This book constitutes the refereed proceedings of the 9th International Conference on Computational Linguistics and Intelligent Text Processing, CICLing 2008, held in Haifa, Israel, in February 2008. The 52 revised full papers presented together with 4 invited papers were carefully reviewed and selected from numerous submissions. The papers cover all current issues in computational linguistics research and present intelligent text processing applications. The papers are organized in topical sections on language resources, morphology and syntax, semantics and discourse, word sense disambiguation and named entity recognition, anaphora and co-reference, machine translation and parallel corpora, natural language generation, speech recognition, information retrieval and question answering, text classification, text summarization, as well as spell checking and authoring aid.